Application of equal opportunities in firms in the Czech Republic - Kmeťová, Michaela; Plášková, Alena, 1949-; Skácelík, Pavel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
This Master's thesis is focused on application of equal opportunities for women and men in firms in the Czech Republic. The purpose is to define the concept of corporate social responsibility as well as equal opportunities. The thesis also introduces the Czech legislation that deals with discrimination and the advantages for companies of complying with equal opportunities for men and women. It is concluded with a research of application of equal opportunities in firms in the Czech Republic and it summarizes the results and introduces recommendations.
Vedoucí práce: Alena Plášková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses